Agrarian policy of the RCP (B) in the Kuban and the Black Sea region in conditions of the transition from war communism to nep: 1920–1924 - Maria S. Dirivyankina (Кавказология, 2023)
The complex of measures applied by the Bolshevik government after the establishment of its power in 1917 and based on military mobilization and violent methods, went down in history as the policy of war communism. Because of this, having re-established Soviet power in 1920 on the territory of the Kuban-Black Sea region, the Bolsheviks faced two main tasks: providing the population of Central Russia with food and solving the land issue, which had to be resolved through the forcible collection of food and egalitarian land use. Introducing military-communist practices in the region met with active resistance from the population. The proclamation in March 1921 of the transition to a new economic policy could not significantly change the situation in the region, since until 1924, when the new course “Facing the Village” was adopted, the relapses of war communism persisted.